If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + 3)(3x + -5) = 0 Reorder the terms: (3 + 2x)(3x + -5) = 0 Reorder the terms: (3 + 2x)(-5 + 3x) = 0 Multiply (3 + 2x) * (-5 + 3x) (3(-5 + 3x) + 2x * (-5 + 3x)) = 0 ((-5 * 3 + 3x * 3) + 2x * (-5 + 3x)) = 0 ((-15 + 9x) + 2x * (-5 + 3x)) = 0 (-15 + 9x + (-5 * 2x + 3x * 2x)) = 0 (-15 + 9x + (-10x + 6x2)) = 0 Combine like terms: 9x + -10x = -1x (-15 + -1x + 6x2) = 0 Solving -15 + -1x + 6x2 = 0 Solving for variable 'x'. Factor a trinomial. (-3 + -2x)(5 + -3x) = 0Subproblem 1
Set the factor '(-3 + -2x)' equal to zero and attempt to solve: Simplifying -3 + -2x = 0 Solving -3 + -2x = 0 Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -2x = 0 + 3 Combine like terms: -3 + 3 = 0 0 + -2x = 0 + 3 -2x = 0 + 3 Combine like terms: 0 + 3 = 3 -2x = 3 Divide each side by '-2'. x = -1.5 Simplifying x = -1.5Subproblem 2
Set the factor '(5 + -3x)' equal to zero and attempt to solve: Simplifying 5 + -3x = 0 Solving 5 + -3x = 0 Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -3x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -3x = 0 + -5 -3x = 0 + -5 Combine like terms: 0 + -5 = -5 -3x = -5 Divide each side by '-3'. x = 1.666666667 Simplifying x = 1.666666667Solution
x = {-1.5, 1.666666667}
| (2x^2y^2-3xy+4)(4xy^2)= | | (2x-1)(x-5)(x-8)=0 | | 2ab+a+5ab+b= | | x^2+35x+19= | | 9-x=1+x+18 | | x=2x-4 | | 78-4x=14x+20 | | 9-9x=41-23x | | 3x+6=62-4x | | 5x+23=13x-73 | | 7x-28=49 | | 4(x-2)=x+5(x-4) | | 3x^2-2x-133=0 | | -2-3x=3-x | | 5(x-15)=-2(18-x) | | -3x-x=3+5x | | y=5x^2-6x-95 | | 2x-yx+4y=12 | | x^2+13x+32=0 | | 9x+10y=74 | | 4-3(4a+5)=5(7-4a) | | 7x+3=3x-21 | | 11(t-3)+3t=7(3t+5)-11 | | -5x^2-25x-30=0 | | -0.0833333x=-1-0.1666666y | | -0.0833333x=-1-0.1666666 | | 17-16x=3-2x | | 0=-2y+4-7x | | -3+3x=-2(x+1) | | .5y-6=.1428571429y | | 6x+7=8x-15 | | 3x^3-36x^2+108x=0 |